Classical Solvability of the First Initial Boundary-Value Problem for a Nonlinear Strongly Degenerate Parabolic Equation - Bazalii, B. V.; Krasnoshchok, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove the existence of a classical solution global in time for the first initial boundary-value problem for a nonlinear strongly degenerate parabolic equation.